Legal Liability of Insurance Companies for Unlawful Acts Arising from the Unilateral Cancellation of Life Insurance Policies: A Study of Decision No. 4943 K/Pdt/2024 - Simanjuntak, Sabriani Royana; Nababan, Roida; Habeahan, Besty (Al-Risalah, 2026)
The development of Indonesian positive law has provided more detailed guidelines regarding procedures for policy cancellation, disclosure obligations, and mechanisms for objections by policyholders, affirming that insurance companies may not unilaterally cancel policies unless supported by clear legal grounds and carried out in accordance with lawful procedures. This study aims to analyze the legal liability of insurance companies for unlawful acts and to examine judicial considerations in Decision No. 4943 K/Pdt/2024. The research employs a normative juridical method using statutory, case, and conceptual approaches, with data obtained through library research and analyzed qualitatively using legal reasoning analysis. The findings indicate that unilateral cancellation of an insurance policy without lawful grounds constitutes a violation of law that gives rise to legal liability for the insurance company, as such actions fulfill all elements of an unlawful act under Article 1365 of the Indonesian Civil Code, namely the existence of an act, fault, damage, and a causal relationship. The Supreme Court emphasized that insurance companies cannot evade liability on unilateral grounds, as the refusal to pay claims and cancellation of policies contradict the principles of pacta sunt servanda and good faith; therefore, insurers are obliged to compensate the injured party. The implications of this decision confirm that the legal liability of insurance companies is firm and cannot be set aside, while also strengthening legal protection for policyholders and reinforcing the application of good faith and legal certainty in insurance practices in Indonesia.